MXene‐Based Nonlinear Optical Information Converter for All‐Optical Modulator and Switcher. Issue 12 (31st October 2018) - Wu, Leiming; Jiang, Xiantao; Zhao, Jinlai; Liang, Weiyuan; Li, Zhongjun; Huang, Weichun; Lin, Zhitao; Wang, Yunzheng; Zhang, Feng; Lu, Shunbin; Xiang, Yuanjiang; Xu, Shixiang; et al.
Abstract: Two‐dimensional (2D) Ti3 C2 T x (T = F, O, or OH) MXene, a graphene‐like material, is successfully fabricated for an investigation in nonlinear optics. Its nonlinear refractive index ( n 2 ≈ 10 −4 [cm 2 W −1 ]) and third‐order nonlinear susceptibility ( χ monolayer ( 3 ) ≈ 10 −7 [e.s.u.]) are experimentally confirmed by spatial self‐phase modulation (SSPM) techniques. Applying its strong Kerr effect, a novel all‐optical switcher based on 2D MXene is designed to realize the modulation of pump light to probe light. This indicates that MXene could act as an information converter in an optical light‐control‐light system. Meanwhile, probe light is induced by the pump light to excite diffraction rings, and the ring numbers of the probe light can be controlled to increase by the regulation of the other pump light. Through modulation of the pump light, the "ON" and "OFF" modes in the all‐optical switcher/modulator can be achieved. This work highlights the potential of Ti3 C2 T x MXene materials applied in all‐optical switcher/modulators, which can be considered an important step toward MXene‐based advanced photonics devices. Abstract : The nonlinear optical response of 2D Ti3 C2 T x (T = F, O, or OH) MXene is investigated with spatial self‐phase modulation techniques for application in advanced photonics devices. Through modulation of the pump light, the "ON" and "OFF" modes in the MXene‐based all‐optical switcher/modulator are achieved.